Antifeedant activity of alkaloid extracts from calafate ( Berberís microphylla , G. Forst, 1789) against diamondback moth larvae ( Plutella xylostella , Linnaeus, 1758) - Manosalva Carrasco, Loreto Ivette Del Carmen; Ana Mutis; Rubén Palma; Fajardo Morales, Victor Manuel; Andrés Quiróz (My University, 2019)
In laboratory by dual choice test, stem and root alkaloid extracts of Berberis microphylla showed antifeedant activity against third-instar Plutella xylostella larvae. Stem extracts showed significantly lower leaf consumptions at concentrations of 500 and 1000 mg/L, as illustrated by antifeedant index of 72 and 97% respectively, whereas, root extracts were significantly active at 100, 500 and 1000 mg/L with antifeedant index of 68, 85 and 99% respectively. In addition, the pure berberine identified as the major alkaloid in the plant extracts showed significant lower food consumption by larvae only at concentration of 1000 mg/L, but the pure palmatine not affect feeding at any concentration. The results suggest that alkaloids extract of B. microphylla have promising antifeedant activity and could by incorporated in an integrated pest management (IPM) programs for P. xylostella.
Keywords: Plutellidae